Lithuanian Language Curricula - Čepaitienė, Giedrė (Lietuvių kalba, 2024)
This article provides an overview of the general secondary school Lithuanian curricula. The very first curricula were developed as early as under the tsar’s rule (in 1906 and 1917). Once the Lithuanian state was restored, school curricula were usually published by the Ministry of Education, with individual schools only occasionally publishing a curriculum of their own. During the Soviet era, curricula were developed solely by the Ministry. Since the restoration of the Lithuanian independence in 1990, the Ministry has maintained its role of developing school curricula and so there have been just a few independently published curricula so far. Notably, curricula are typically anonymous. We know the authors of the first two curricula: the curriculum for the academic year 1905–1906 at Panevėžys Teacher Training Seminary was designed by Vladimiras Lukinas, and the following year, the curriculum for the same seminary was developed by Jonas Jablonskis. After 1990, curricula have usually been developed by working groups established by the Ministry; the lists of their members are publicly available. The article highlights the structure, didactic attitudes, and the organization of topics within the curricula, and demonstrates that the authors of the first curricula followed the descriptive work on the Lithuanian language already published at the time, whereas once the Ministry of Education began publishing curricula, they themselves became guidelines for textbook authors. The trend remains the same to this day.